DESIGN OF AN AUTOMATIC ATTENDANCE SYSTEM AT PRINGSEWU POLICE DEPARTMENT USING RFID - Nugroho, Imam; Susianto, Didi; Puspitasari, Tuti (Jurnal TAM (Technology Acceptance Model), 2025)
The manual attendance system used at the Pringsewu Police Department still has several weaknesses, such as potential data manipulation, delays in attendance recapitulation, and reliance on inefficient manual recording processes. This study aims to design and develop an automatic attendance system based on Radio Frequency Identification (RFID) technology that can record personnel attendance in real-time, accurately, and in an integrated manner. The method used is Research and Development (R&D) with ten stages, starting from data collection through observation, interviews, and literature review, as well as system design using UML models. The system is built using RFID RC522 hardware, ESP32 microcontroller, and a WiFi network connected to a web server with applications based on PHP and MySQL. The system workflow is illustrated through use case diagrams, sequence diagrams, and class diagrams, demonstrating that the system can read RFID cards, automatically record attendance data into the database, and generate reports accessible by the admin via a dashboard. Users found the system easy to use and supportive of work efficiency. The study concludes that the RFID-based automatic attendance system is effective in replacing the manual method. In the future, the system can be further developed with additional features and integrations to support broader implementation.